The impact of vision impairment on depressive symptoms among older adults: The mediating role of dispositional optimism. - Xi Ji; Yujie Zhang (PLoS ONE, 2025)
Background Vision impairment, beyond constituting a sensory deficit, fundamentally disrupts older adults' autonomy, emotional regulation, and social participation. These disruptions increase vulnerability to depressive symptoms. While the adverse mental health consequences of sensory decline are well-documented, the psychological mechanisms underlying this association remain insufficiently examined. Dispositional optimism-a stable cognitive-affective trait characterized by generalized positive future expectations-may serve as a key mediator, promoting resilience through adaptive appraisal and emotional regulation processes. Objective This study examines the mediating role of dispositional optimism in the relationship between vision impairment and depressive symptoms among older adults, and explores how its buffering effects vary by perceived control and socioeconomic resources. The findings aim to inform the integration of psychological resilience frameworks into geriatric mental health care and vision rehabilitation programs. Methods This study used panel data from 7,205 older adults in the 2014 and 2018 waves of the Chinese Longitudinal Healthy Longevity Survey (CLHLS). Depressive symptoms were assessed using a harmonized CES-D scale, vision impairment through a field-based functional vision screening, and dispositional optimism via a 5-point Likert item. Ordered logit regression and bootstrapped mediation models were employed to estimate both direct and indirect effects, with subgroup analyses conducted to test for moderation by perceived control and socioeconomic status. Results Vision impairment was significantly associated with increased depressive symptoms (β = -0.218, p < 0.001). Dispositional optimism mediated 24.7% of this effect (indirect effect = -0.004, p < 0.01), indicating its role as a psychological buffer. The protective function of optimism was more pronounced among individuals with higher perceived control (β = -0.135, p < 0.05), higher educational attainment (β = 0.264, p < 0.001), and better economic status (β = 0.210, p < 0.001). Notably, even among individuals with low perceived control, optimism continued to significantly mitigate depressive symptoms (indirect effect = -0.002, p < 0.05). Conclusion These findings reveal the importance of incorporating psychological resources into vision care strategies for older adults-particularly the oldest-old and those in socioeconomically disadvantaged contexts. Interventions aimed at fostering dispositional optimism, such as cognitive-behavioral techniques, may enhance emotional resilience, reduce depression risk, and improve quality of life in aging populations experiencing sensory decline.